Phonological awareness in Urdu language speaking children with down syndrome (DS) - Maimoona Khalil; Nazia Mumtaz; Ghulam Saqulain; Farheen Naz Anis (PLoS ONE, 2026)
Introduction Phonological awareness (PA) is a vital part of literacy development. With dearth of evidence on phonological processing among Urdu-speaking children with down syndrome (DS), current study was conducted to determine the association between response time on rapid naming tasks and phonological awareness performance in children with Down syndrome. Methods A quasi-experimental study that used cross-sectional design was carried out with 48 children with DS and who are Urdu speaking children (4–12 years) at three rehabilitation centers in Lahore, Pakistan. Rapid automatized naming and phoneme identification tasks were measured with the help of the Urdu Phonological Tele-Assessment (U-PASS) tool. Simple linear regression and partial correlation were analyzed. Results The results revealed that the mean response time and phonological awareness had no significant relationship (R2 = 0.006, p = 0.587). The phoneme recognition (M = 9.42) at the beginning was much higher than the phoneme recognition (M = 5.42) at the end. There was moderate positive correlation existing between initial and final phoneme awareness (r = 0.423, p = 0.004) that did not depend on response time. Conclusion Processing speed processing and phonological accuracy are two different cognitive constructs in children with DS. The clinicians are encouraged to emphasize the accuracy-based testing and adopt specific interventions addressing the end phoneme awareness.